PERUBAHAN PREVALENSI GONDOK DARI TAHUN 1980 SAMPAI TAHUN 1998 - Muhilal Muhilal; Dini Latief; Djoko Kartono; Dewi Permaesih (Persagi, 1999)
Change in The Goitre Prevalence among School Children 1990-1998.Iodine deficiency disorders (IDD) is major nutritional problem in many part of Indonesia. Iodised oil distribution and salt iodination are the two programs to control IDD. Surveys to evaluate the impact of IDD control programs have been conducted three times in 1982, 1990 and 1998. Indicator used in the survey was Total Goitre Rate (TGR) amongst school children at sub-district level. This paper analysed data of three surveys for the same sub-district only. Fifty-nine sub-districts surveyed in 1980 and then resurveyed in 1988 and 1998 were analysed to observe the changes in the TGR over the time. The results showed that the mean TGR in 1980, 1988 and 1998 were 33.1%, 30.3% and 17.7% respectively. Overall percentage of sub-district with TGR less than 5% in the 3 surveys was 0%, 13.6% and 32.2% respectively. For Java-Bali region that represent the better development in communication infrastructure, the mean TGR in the 3 surveys were 31.6%, 25.7% and 9.9% respectively. Percentage of sub-district with TGR less than 5%, for Java-Bali region, was 0%, 16.7% and 44.0%. For outside Java-Bali region, the mean TGR were 33.7%, 32.3% and 21.1% respectively. Percentage of sub-district with TGR less than 5%, for outside Java-Bali region, was 0%, 12.2% and 26.8%. In 1998, about two-third of salt consumed by household contained adequate iodine (30 ppm). The relationship between TGR and percentage of salt with 30 ppm of iodine was fairly high (r=0.66).Keywords: goitre, school children, change, region